Host stress and immune responses during aerosol challenge of Brown Norway rats with Yersinia pestis - Gater, Susan T.; Peters, Kristen N.; Kocsis, Andrew G.; Dhariwala, Miqdad O.; Anderson, Deborah M.; Anderson, Paul E. (Frontiers in Cellular and Infection Microbiology, 2012)
Inhalation exposure models are becoming the preferred method for the comparative study of respiratory infectious diseases due to their resemblance to the natural route of infection. To enable precise delivery of pathogen to the lower respiratory tract in a manner that imposes minimal biosafety risk, nose-only exposure systems have been developed. Early inhalation exposure technology for infectious disease research grew out of technology used in asthma research where predominantly the Collison nebulizer is used to generate an aerosol by beating a liquid sample against glass. Although infectious aerosol droplets of 1-5µm in size can be generated, the Collison often causes loss of viability. In this work, we evaluate a gentler method for aerosolization of living cells and describe the use of the Sparging Liquid Aerosol Generator (SLAG) in a rat pneumonic plague model. The SLAG creates aerosols by continuous dripping of liquid sample on a porous metal disc. We show the generation of 0.5 to 1µm Y. pestis aerosol particles using the SLAG with spray factors typically ranging from 10-7 to 10-8 with no detectable loss of bacterial viability. Delivery of these infectious particles via nose-only exposure led to the rapid development of lethal pneumonic plague. Further, we evaluated the effect of restraint-stress imposed by the nose-only exposure chamber on early inflammatory responses and bacterial deposition. Elevated serum corticosterone which peaked at 2 hrs post-procedure indicated the animals experienced stress as a result of restraint in the nose-only chamber. However, we observed no correlation between elevated corticosterone and the amount of bacterial deposition or inflammation in the lungs. Together these data demonstrate the utility of the SLAG and the nose-only chamber for aerosol challenge of rodents by Y. pestis.